THE CONCEPT OF ISLAMIC LAW THOUGHT OF SAYYID SABIQ IN THE BOOK OF FIQH SUNNAH (ANALYTICAL STUDY IN DISTINGUISHING BID'AH AND IKHTILAF) - Zulfikar Zulfikar (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
Sayyid Sabiq is a fiqh sunnah writer who strived to be an enlightener on the rise of taqlid (an Islamic term denoting the conformity of one person to the teaching of another) and the closing door to ijtihad (an Islamic legal term referring to independent reasoning or the thorough exertion of a jurist's mental faculty in finding a solution to a legal question) for Muslims. Muslims at that time disbelieved each other and always rubbed against differences in maddhab (a school of thought within fiqh; Islamic jurisprudence). Regarding ikhtilaf (an Islamic scholarly religious disagreement), according to Sayyid Sabiq there are forbidden ikhtilaf as well as the allowed one. Sayyid Sabiq's Concept of Islamic Law tends to be strict on certain legal issues and loose on others. This paper is classified as normative Islamic law research with a conceptual and philosophical-logical approach. The method of data analysis used in this research is the deductive-inductive method. The results of the study concluded that according to Sayyid Sabiq; the permanent Islamic law that cannot be changed has criteria as follows; a) has been explained in detail by nass (sentences from the Quran or hadith that are used as reasons or the basis for deciding a problem, as a guide in sharia law), b) the laws of aqidah (creed) and worship, c) all laws whose nass status is qaṭ'ī ad-dilalah. Meanwhile, the dynamic Islamic law which follows changes in time and place has criteria as follows; a) laws that are only explained by the nass globally, b) laws on civil benefit, siyasa (politics), war and justice, c) and all the laws whose nass status is annī ad-dilalah. Sayyid Sabiq's thoughts applied the integration of fiqh with aqidah (creed) and morals. That means, the substance of his thought has succeeded in eradicating the dichotomy of fiqh with other elements of Islamic teachings.